2019
DOI: 10.1155/2019/5631723
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Impact Time and Angle Control Guidance Based on MPSP

Abstract: A new nonlinear guidance law for air-to-ground missile cooperation attacks is proposed in this paper. This guidance law enables missiles with different initial conditions to attack targets simultaneously, and it can also precisely satisfy the terminal impact angle conditions in both flight-path angle and heading angle. The guidance law is devised using the model predictive static programming (MPSP) method, and the control saturation constraint is incorporated in the MPSP algorithm. The first-order-lag accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Adding (21) into (24) and rearranging it, it can be found that the terminal state variation can be expressed as a linear function of the deviation of initial state , , ,…”
Section: B Linear Pseudospectral Model Predictive Spread Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding (21) into (24) and rearranging it, it can be found that the terminal state variation can be expressed as a linear function of the deviation of initial state , , ,…”
Section: B Linear Pseudospectral Model Predictive Spread Controlmentioning
confidence: 99%
“…Therefore, it has high computational efficiency in comparison with the conventional numerical methods and dynamic programming approach. Also, this method has been successfully applied to formulate several optimal guidance laws with terminal angle constraint [6], [19]- [21]. However, to ensure the Euler integration within a desired precision limitation, a large number of discrete points should be selected for MPSP.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the model predictive static programming (MPSP) paradigm has been extensively applied to the field of constrained vehicle guidance, yielding significant advancements. A novel nonlinear guidance law has been formulated utilizing MPSP, facilitating the simultaneous arrival of missiles with diverse initial conditions at their targets, while adhering to terminal impact angle constraints [18]. Building upon the variable time MPSP framework [19], a guidance law has been engineered for three-dimensional nonlinear guidance challenges, incorporating the expected attack time into the objective function to address constraints on both attack time and angle [20].…”
Section: Introductionmentioning
confidence: 99%
“…Departing from controlling remaining flight time, the modified model predictive control (MPC) is adopted to make state variables converge over time, aiming for the simultaneous interception [11]. In a three-dimensional scenario, the model predictive static programming (MPSP) method is used to explore guidance laws incorporating remaining flight time and attack angle constraints [12]. Moreover, cooperative guidance laws incorporating both attack angle and line-of-sight constraints were separately focused, with limited-time convergence guidance laws proposed [13,14].…”
Section: Introductionmentioning
confidence: 99%